Fostering teacher–student relationship-building competence: a three-year learning trajectory for initial pre-primary and primary teacher education - Borremans, Liedewij F. N.; Koomen, Helma M. Y.; Spilt, Jantine L. (Frontiers in Education, 2024)
It is widely acknowledged that high-quality teacher-student relationships contribute to both student and teacher well-being. However, research shows that building these relationships can be challenging for teachers and signals opportunities for teacher education to better prepare them for building high-quality teacher-student relationships.As teachers' relationship-building competence allows them to establish high-quality relationships with students, even those typically at-risk for conflictual relationships, we propose a learning trajectory targeting teachers' dyadic relationship-building competence to be implemented in initial teacher education. Such a learning trajectory allows for progressively deepening the level of understanding and self-reflection throughout the three-year initial education program.To address teachers' relationship-building competence in teacher education, relevant competencies, selected in previous research by an independent expert panel (Borremans & Spilt, 2023), were translated into specific learning goals, learning activities, and materials in close collaboration with partner university colleges. An overview of planned quantitative and qualitative data collection is presented. The learning trajectory could strengthen initial pre-primary and primary teacher education programs in supporting pre-service teachers' relationship-building competence.